Antimicrobial activity of plants infusions on oral fusobacteria and their adherence to human erythrocytes - Gaetti-Jardim Júnior, Elerson [UNESP]; Landucci, Luis Fernando; Okamoto, Ana Cláudia [UNESP]; Akeshigue, Haroldo (My University, 2013)
Periodontal disease is the result of the interrelationship between microbiotic aggression and the host’s organic defence. Amongst the microorganisms involved in periodontopathies, Fusobacterium nucleatum is conspicuous by establishing a link between the initial and final colonizers, besides producing toxic compounds and adhering to the host’s cells. Control of bacterial biofilm can be achieved by use of chemical agents, many of which extracted from plants. Thus the object of this study was to evaluate the inhibitory activity in vitro of some teas, generally taken in a normal diet, on Fusobacterium nucleatum and your adherence to host’s cells. Minimum inhibitory and bactericidal concentrations were established and haemagglutinative test in microplaques was effected. It was ascertained that all plant extracts have inhibitory activity and that infusions of Camellia sinensis (black tea and green tea), Mentha piperita (mint) and Pimpinella anixem (aniseed) added to the bacteria/erythrocyte compound reduced significantly the adherence of microorganisms.

La enfermedad periodontal es el resultado de la interrelación entre la agresión microbiana y la defensa ecológica del huésped. Entre los microorganismos implicados en periodontopatías, Fusobacterium nucleatum es visible mediante el establecimiento de un enlace entre los colonizadores iniciales y finales, además de producir compuestos tóxicos y de adherirse a las células del huésped. Control de la biopelícula bacteriana se puede lograr mediante el uso de agentes químicos, muchos de los cuales se extraen de plantas. Así, el objeto de este estudio fue evaluar la actividad inhibidora in vitro de algunos tipos de té, generalmente adoptadas en una dieta normal, por Fusobacterium nucleatum y su adherencia a las células huésped. Las concentraciones mínimas inhibitorias y bactericidas se establecieron y prueba haemagglutinative en microplacas fue efectuada. Se comprobó que todos los extractos de plantas tienen actividad inhibidora y que las infusiones de Camellia sinensis (té negro y té verde), Mentha piperita (menta) y Pimpinella anixem (anís) añadido a las bacterias / compuesto de eritrocitos redujo significativamente la adherencia de microorganismos.

Atividade antimicrobiana de infusões de vegetais sobre fusobactérias bucais e sua capacidade de adesão a eritrócitos humanos
Actividad antimicrobiana de infusiones vegetales en fusobacterias orales y su capacidad de adhesión a los eritrocitos humanos
Atividade antimicrobiana de infusões de vegetais sobre fusobactérias bucais e sua capacidade de adesão a eritrócitos humanos
Keywords: Dental plaque; Periodontitis; Disease prevention; Plant extracts; Hemagglutination; Cell adhesion; Placa dental; Periodontitis, prevención de enfermidades; Extractos vegetales; Hemaglutinación; Adhesión celular; Placa dentária; Periodontite; Prevenção de doenças; Extratos vegetais; Hemaglutinação; Adesão celular